Towards a Model of Valued Human Cognitive Abilities: An African Perspective Based on a Systematic Review - Oppong, Seth (Frontiers in Psychology, 2020)
Studies that investigate cognitive ability in African children and estimate the general cognitive abilities of African adults tend to work with existing models of intelligence. However, African philosophy and empirical studies in cross-cultural psychology have demonstrated that conceptualizations of human cognitive ability vary with location. This paper begins with the assumption that the existing Anglo-American models of cognitive abilities are valuable but limited in their capacity to account for the various conceptualizations of valued cognitive abilities in different human societies. On the basis of this assumption, I employ extant empirical evidence generated through ethnographic studies across Africa to formulate what an African model of valued human cognitive ability ought to be. The output of this formulation has been so christened a model of valued cognitive ability in order to draw attention to the fact that models of cognitive abilities have currency and values in each human society. This value allocation is expected to influence which elements of cognitive ability each human society will promote and develop. In addition, implications for theory, research and praxes are discussed.